Impak Sosioekonomi Program Penempatan Tersusun: Kajian Kes Masyarakat Orang Asli di Parlimen Cameron Highlands - Krishnasamy, Devamany S. (2013)
Among the governmental strategy to enhance the quality of life of the indigenous community is the implementation of the Resettlement Plan (RPS) and Village Reconstruction (PPK). RPS involves the relocation of remote aboriginal communities scattered in an area and equipped them with basic amenities and economic activities for commercial agriculture in a specific location. While in PPK the settlements are restructured amenities and homes with additional socio infra components. However, infrastructure and social amenities assistance including houses and the location of RPS or PPK among indigenous communities may not be compatible with the choices they desire. In addition, their living standards may not have a significant change in the resettlement vicinity. After about 35 years of implementation, this study will evaluate the impact of settlement/restructuring of indigenous peoples in the RPS and PPK, located in the Parliament of Cameron Highlands, Pahang. This study design is a descriptive quantitative and qualitative one using case study methodology (surveys/field). Impact and satisfaction of the relocation program is evaluated using five indicators in terms of economic opportunities, social relationships, ability to maintain tradition, public utility services and satisfaction with the size/location of the village/house in the settlement area. In general, the results show that the RPS and the PPK have managed to improve the quality of life of indigenous community. Study finds that Aboriginal satisfaction has increased compared to their previous village dwellings. However, these achievements are still low when compared with the same indicators at the national level. In fact, the study found that indigenous communities living in the RPS are more successful than the PPK.